(untitled) (Research, Society and Development, 2022)
Sepsis is defined as a dysfunction of the organism caused by a deregulated response to infection, in different clinical stages of the same pathophysiological process. The present study aimed to describe the signs and symptoms that precede sepsis that nursing professionals can identify early in patients hospitalized in Intensive Care Units - ICUs. Methodology: This is a narrative review of the literature based on a literature search based on a literature search carried out in July 2020 in the respective data sources: Medical Literature Analysis and Retrieval System Oline (Medline) and Scientific Electronic Library Online (SciELO). Results: Because nurses work directly with bedside patient care, they are able to identify the first clinical changes in signs and symptoms that precede sepsis, such as: tachycardia (88.5%), tachypnea (79.2%), oliguria (78.1%), hypothermia (75.2%), hypotension (67.1%), hyperthermia (30.2%), desaturation (12.7%), Lowering of the Level of Consciousness (RNC) (5.5%). However, nursing professionals have some difficulty in the early identification of sepsis in the Intensive Care Unit (ICU), either because of the complexity of the patient, lack of protocol in some institutions or even lack of knowledge about this clinical process.